Study of radiative bottomonium transitions using converted photons - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We use (111±1) million Υ(3S) and (89±1) million Υ(2S) events recorded by the BABAR detector at the PEP-II B-factory at SLAC to perform a study of radiative transitions between bottomonium states using photons that have been converted to e+e− pairs by the detector material. We observe Υ(3S)→γχb0,2(1P) decay, make precise measurements of the branching fractions for χb1,2(1P,2P)→γΥ(1S) and χb1,2(2P)→γΥ(2S) decays, and search for radiative decay to the ηb(1S) and ηb(2S) states.
Gesehen am 08.08.2022